2‐(N‐Methylbenzyl)pyridine: A Potential Liquid Organic Hydrogen Carrier with Fast H2 Release and Stable Activity in Consecutive Cycles. Issue 4 (18th January 2018) - Oh, Jinho; Jeong, Kwanyong; Kim, Tae Wan; Kwon, Hyunguk; Han, Jeong Woo; Park, Ji Hoon; Suh, Young‐Woong
Abstract: The liquid organic hydrogen carrier (LOHC) 2‐( N ‐methylbenzyl)pyridine (MBP) shows good potential for H2 storage based on reversible hydrogenation and dehydrogenation, with an H2 storage density of 6.15 wt %. This material and the corresponding perhydro product (H12 ‐MBP) are liquids at room temperature. Remarkably, H2 release is much faster from H12 ‐MBP over Pd/C than from the benchmark perhydro benzyltoluene over Pt/C at lower temperatures than 270 °C, owing to the addition of N atom into the benzene ring. Since this positive effect is unfavorable to the hydrogenation reaction, more Ru/Al2 O3 catalyst or prolonged reaction time must be applied for complete H2 storage. Experiments with repeated hydrogenation–dehydrogenation cycles reveal that reversible H2 storage and release are possible without degradation of the MBP/H12 ‐MBP pair. The prepared MBP satisfies the requirements for chemical stability, handling properties, and cytotoxicity testing. Abstract : It could've been a brilliant carrier : A new liquid organic hydrogen carrier is designed by adding N atom into the benzene ring of a benchmark heat‐transfer fluid. The crossover between H2 ‐lean and H2 ‐rich forms of the title material is reversible in repeated runs. Notably, the reduced dehydrogenation enthalpy, owing to the presence of N, leads to very fast H2 release, indicating excellent potential for efficient H2 storage.